MENGENALI JENIS-JENIS BULLYING DI SEKOLAH DASAR DAN CARA MENGATASINYA - Agustin, Angelia; Saputri, Annisa Indah; Azzahra, Ummu Darda; Supriyadi, Supriyadi; Izzatika, Amrina (JS (JURNAL SEKOLAH), 2024)
Abstract : This research aims to identify/recognize the types of bullying in elementary schools and how to overcome them. This type of research is a type of library research, namely searching and browsing literature by reading various books, journals and other publications related to the research subject. The results of the research indicate that bullying is a complex phenomenon involving abuse of power and disturbing consequences for both victims and perpetrators. The identified types of bullying, such as physical, verbal and relational bullying, demonstrate the various ways in which violations can be committed in the school environment. Factors that incite bullying include the child's temperament, parenting style in the family, the influence of peers, as well as the impact of mass media and a school climate that is not conducive. To overcome this problem, it is important for schools to implement preventive measures, including character development through regular activities and ethics seminars. Apart from that, the presence of clear policies and support from parents as well as the active participation of teachers are vital in creating a secure and harmonious study environment. This research contributes significantly to understanding the phenomenon of bullying among elementary school students by identifying various forms, causes and impacts. It is hoped that these findings will provide a basis for the elaboration of more effective prevention and intervention strategies in schools, in order to create a harmonious study environment for all students. Keywords: Types of Bullying, Elementary School, Preventive Abstrak : Penelitian ini bertujuan untuk mengidentifikasi/mengenali jenis-jenis bullying di sekolah dasar dan cara mengatasinya. Jenis penelitian ini merupakan jenis penelitian studi kepustakaan (library research) yaitu pencarian dan penelusuran literatur dengan cara membaca berbagai buku, jurnal, dan publikasi lain nan berasosiasi dengan subjek penelitian. Hasil penelitian mengindikasi bahwa bullying merupakan fenomena kompleks nan melibatkan penyalahgunaan kekuasaan dan imbas yang mengalutkan baik bagi korban maupun eksekutor. Jenis-jenis bullying yang teridentifikasi, seperti bullying fisik, verbal, dan relasional, menunjukkan berbagai cara pelanggaran yang dapat dilakukan di lingkungan sekolah. Faktor-faktor yang menghasut sikap bullying mencakup temperamen anak, pola asuh dalam keluarga, pengaruh teman sebaya, serta dampak media massa dan iklim sekolah yang tidak kondusif. Untuk mengatasi masalah ini, penting bagi sekolah untuk menerapkan langkah-langkah preventif, termasuk pengembangan karakter melalui kegiatan rutin dan seminar etika. Selain itu, kehadiran kebijakan yang jelas dan dukungan dari orang tua serta partisipasi aktif guru menjadi vital dalam mewujudkan lingkungan studi nan terjaga dan harmonis. Penelitian ini berkontribusi signifikan dalam memahami fenomena bullying di kalangan siswa sekolah dasar dengan mengidentifikasi berbagai bentuk, penyebab, dan dampaknya. Temuan ini diharapkan dapat menggambarkan landasan bagi elaborasi strategi pencegahan dan intervensi yang lebih ampuh di sekolah, demi melahirkan lingkungan studi nan harmoni bagi semua siswa. Kata Kunci : Jenis-jenis Bullying, Sekolah Dasar, Preventif